Pandangan Dunia Diaspora Palestina–Lebanon dalam Puisi Li Bayrūt Masā’ al-Khayr Karya Marwan Makhoul (Kajian Strukturalisme Genetik) - Yaskur, Muhammad Yazid; Asrina, Asrina (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2026)
Contemporary Palestinian poetry represents diverse diasporic experiences shaped by specific social and historical contexts of displacement. One particularly distinctive context is the Palestinian diaspora in Lebanon, which has been profoundly shaped by the 1948 Nakba and prolonged structural marginalization across generations. The poem Li Bayrūt Masā’ al-Khayr by Marwan Makhoul reflects this condition through the symbolic articulation of a Palestinian–Lebanese identity within a single body. This study aims to examine the worldview of the Palestinian diaspora in Lebanon using a genetic structuralism approach. Employing a qualitative descriptive method, the research relies on library research and textual analysis of the poem’s lines. The findings reveal that the poem articulates a collective consciousness shaped by the trauma of the Nakba, a prolonged period of historical estrangement spanning from 1948 to the late twentieth century, and a generational crisis of orientation. Moreover, the poem expresses an anti-romantic stance toward suffering, signaling a new ideological consciousness that departs from earlier generations of Palestinian poetry that tended to aestheticize pain and heroic sacrifice. The study concludes that Li Bayrūt Masā’ al-Khayr functions as a medium for articulating a historically grounded, critical, and ethical collective worldview of the Palestinian–Lebanese diaspora. The implications of this research highlight the continued relevance of genetic structuralism in analyzing conflict poetry as a dialectical expression of literary structure, historical experience, and generational shifts in worldview.